2014
DOI: 10.1088/1478-3975/11/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

The Goodwin model revisited: Hopf bifurcation, limit-cycle, and periodic entrainment

Abstract: The three-variable Goodwin oscillator is a minimal model demonstrating the emergence of oscillations in simple biochemical feedback systems. As a prototypical oscillator, this model was extensively studied from a theoretical point of view and applied to various biological systems, including circadian clocks. Here, we reexamine this model, derive analytically the amplitude equation near the Hopf bifurcation and investigate the effect of a periodic modulation of the oscillator. In particular, we compare the entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…5), the major difference between HT and PS models has not been reported or investigated, to our knowledge. Future work can also investigate whether PS models follow the entrainment properties [37,45,47,142,[156][157][158] or temperature compensation mechanisms [38,40,42,[159][160][161][162][163][164][165][166] identified with HT models. Furthermore, stochastic simulations of HT models commonly indicate that circadian clocks can maintain rhythms even with low numbers of molecules [167][168][169][170].…”
Section: Resultsmentioning
confidence: 99%
“…5), the major difference between HT and PS models has not been reported or investigated, to our knowledge. Future work can also investigate whether PS models follow the entrainment properties [37,45,47,142,[156][157][158] or temperature compensation mechanisms [38,40,42,[159][160][161][162][163][164][165][166] identified with HT models. Furthermore, stochastic simulations of HT models commonly indicate that circadian clocks can maintain rhythms even with low numbers of molecules [167][168][169][170].…”
Section: Resultsmentioning
confidence: 99%
“…Analytical amplitude estimates for specific systems typically require a separate treatment of different parameter regimes, e.g., regions close to the Hopf bifurcation [33] or the limit of strong feedback [34]. Hence, it is often elusive how the details of the nonlinear feedback govern the oscillation amplitude.…”
mentioning
confidence: 99%
“…Stochastic simulations of this circuit revealed parameters that resulted in oscillatory behavior (Figures 4A and S6A; Methods). In addition, deterministic modeling and bifurcation analysis confirmed that this circuit is capable of oscillations (limit cycle oscillations or damped oscillations) (Figure S6B and Methods) ( 29, 30 ). When stochasticity is considered, oscillations (due to “stochastic resonance”) can occur even under parameter regimes that are predicted to not oscillate according to deterministic models ( 3133 ), thereby suggesting that in this circuit, stochasticity together with the appropriate coupling (i.e., governing the PoV) between genes X and Y can give rise to oscillations beyond classic “limit cycle” mechanisms.…”
mentioning
confidence: 82%